Evaluating Views of Teacher Trainees on Teacher Training Process in Turkey - Kä±ldan, Abdullah Oäÿuz; Ä°bret, Bilgin Ãœnal; Pektaåÿ, Murat; Aydä±nã¶zã¼, Duran; Ä°ncikabä±, Lã¼tfi; Recepoäÿlu, Ergã¼n (Edith Cowan University, 2013)
The views of the teacher trainees who have recently started the teaching profession on teacher training process are of great value because they are new graduates and they are in their first year in the profession. Since the teachers in their first year in the profession do not have any experience, they have to pursue the educational tasks based on the knowledge and skills they acquired in their faculties. The main purpose of the study is to evaluate the views of the teacher trainees on the process of teacher training in Turkey.Being qualitative in nature, the current research was a descriptive study. The study group involved 58 newly-appointed teacher trainees from different branches who began their teaching profession in Kastamonu in 2010. An "Interview Form" was used for data collection. The data collected from the participants were analysed through Nvivo 9 software package. As a result of the study, the teacher trainees indicated that they felt insufficient especially related to curriculum and content knowledge and that teaching practice and school experience courses do not adequately contribute to their profession
Keywords: Teacher training; faculties of education; Teacher Education and Professional Development; views of teacher trainees; Education; 4. Education